Soil Texture Alters the Impact of Salinity on Carbon Mineralization - Ruihuan She; Yongxiang Yu; Chaorong Ge; Huaiying Yao (Agronomy, 2021)
Soil salinization typically inhibits the ability of decomposer organisms to utilize soil organic matter, and an increase in soil clay content can mediate the negative effect of salinity on carbon (C) mineralization. However, the interactive effects of soil salt concentrations and properties on C mineralization remain uncertain. In this study, a laboratory experiment was performed to investigate the interactive effects of soil salt content (0.1%, 0.3%, 0.6% and 1.0%) and texture (sandy loam, sandy clay loam and silty clay soil with 6.0%, 23.9% and 40.6% clay content, respectively) on C mineralization and microbial community composition after cotton straw addition. With increasing soil salinity, carbon dioxide (CO2) emissions from the three soils decreased, but the effect of soil salinity on the decomposition of soil organic carbon varied with soil texture. Cumulative CO2 emissions in the coarse-textured (sandy loam and sandy clay loam) soils were more affected by salinity than those in the fine-textured (silty clay) soil. This difference was probably due to the differing responses of labile and resistant organic compounds to salinity across different soil texture. Increased salinity decreased the decomposition of the stable C pool in the coarse-textured soil, by reducing the proportion of fungi to bacteria, whereas it decreased the mineralization of the active C pool in the fine-textured soil through decreasing the Gram-positive bacterial population. Overall, our results suggest that soil texture controlled the negative effect of salinity on C mineralization through regulating the soil microbial community composition.